Polyploidy-associated paramutation in Arabidopsis is determined by small RNAs, temperature, and allele structure - Bente, Heinrich (PLoS Genet, 2021)
Paramutation is a form of non-Mendelian inheritance in which the expression of a paramutable allele changes when it encounters a paramutagenic allele. This change in expression of the paramutable alleles is stably inherited even after segregation of both alleles. While the discovery of paramutation and studies of its underlying mechanism were made with alleles that change plant pigmentation, paramutation-like phenomena are known to modulate the expression of other traits and in other eukaryotes, and many cases have probably gone undetected. It is likely that epigenetic mechanisms are responsible for the phenomenon, as paramutation forms epialleles, genes with identical sequences but different expression states. This could account for the intergenerational inheritance of the paramutated allele, providing profound evidence that triggered epigenetic changes can be maintained over generations. Here, we use a case of paramutation that affects a transgenic selection reporter gene in tetraploid Arabidopsis thaliana. Our data suggest that different types of small RNA are derived from paramutable and paramutagenic epialleles. In addition, deletion of a repeat within the epiallele changes its paramutability. Further, the temperature during the growth of the epiallelic hybrids determines the degree and timing of the allelic interaction. The data further make it plausible why paramutation in this system becomes evident only in the segregating F2 population of tetraploid plants containing both epialleles. In summary, the results support a model for polyploidy-associated paramutation, with similarities as well as distinctions from other cases of paramutation.